Intelligent connectivity : AI, IoT, and 5G - Yarali, Abdulrahman (Hoboken, NJ, USA : Wiley, 2022)
"This book focuses on the fusion between the core technologies of the future ? Artificial Intelligence (AI), 5G, and the Internet of Things (IoT), exploring how they can be mutually supportive. AI, IoT, and 5G are the pillars that lead digital transformation, and the combination of super-fast 5th generation networks with AI and IoT will usher in a new age of intelligent connectivity, particularly beneficial to transportation, logistics, education, healthcare, entertainment, public safety/security and industrial and manufacturing operations. The book will offer technical and economic insights about intelligent connectivity as a key part of transformation in the 4th industrial revolution. The reader (technical and non-technical) will benefit from a comprehensive discussion of Artificial Intelligence, 5G, IoT and machine-learning and how they are vital in the period of open-source programming and moderate cloud computing"--
Preface -- Acknowledgement -- Introduction -- 1 Technology Adoption and Emerging Trends -- 1.1 Introduction -- 1.2 Trends in Business technology -- 1.3 AI-Fueled Organizations -- 1.4 Connectivity of Tomorrow -- 1.5 Moving Beyond Marketing -- 1.6 Cloud Computing -- 1.7 Cybersecurity, Privacy, and Risk Management -- 1.8 Conclusion -- 2 Telecommunication Transformation and Intelligent Connectivity -- 2.1 Introduction -- 2.2 Cybersecurity Concerns in the 5G World -- 2.3 Positive Effects of Addressing Cybersecurity Challenges in 5G -- 2.4 Intelligent Connectivity Use-Cases -- 2.5 Industrial and Manufacturing Operations -- 2.6 Healthcare -- 2.7 Public Safety and Security -- 2.8 Conclusion -- 3 The Internet of Things (IoT): Potentials and the Future Trends -- 3.1 Introduction -- 3.2 Achieving the Future of IoT -- 3.3 Commercial Opportunities for IoT -- 3.4 The Industrial Internet of Things -- 3.5 Future Impact of IoT in Our Industry -- 3.6 Data Sharing in the IoT Environment -- 3.7 IoT Devises Environment Operation -- 3.8 Interoperability Issues of IoT -- 3.9 IoT-Cloud -Application -- 3.10 Regulation and Security Issues of IoT -- 3.11 Achieving IoT Innovations While Tackling Security and Regulation Issues -- 3.12 Future of IoT -- 3.13 Conclusion -- 4 The Wild Wonders of 5G Wireless Technology -- 4.1 Introduction -- 4.2 5G Architecture -- 4.3 5G Applications -- 4.4 5G Network Architecture -- 4.5 Security and Issues of 5G -- 4.6 IoT Devices in 5G Wireless -- 4.7 Big Data Analytics in 5G -- 4.8 AI Empowers a Wide Scope of Use Cases -- 4.9 Conclusion -- 5 Artificial Intelligence Technology -- 5.1 Introduction -- 5.2 Core Concepts of Artificial Intelligence -- 5.3 Machine Learning and Applications -- 5.4 Deep Learning -- 5.5 Neural Networks Follow a Natural Model -- 5.6 Classifications of Artificial Intelligence -- 5.7 Trends in Artificial Intelligence -- 5.8 Challenges of Artificial Intelligence -- 5.9 Funding Trends in Artificial Intelligence -- 5.10 Conclusion -- 6 AI, 5G, & IoT: Driving Forces Towards the Industry Technology Trends -- 6.1 Introduction -- 6.2 Fifth Generation of Network Technology -- 6.3 Internet of Things (IoT) -- 6.4 Industrial Internet of Things -- 6.5 IoT in Automotive -- 6.6 IoT in Agriculture -- 6.7 AI, IoT, and 5G Security -- 6.8 Conclusion -- 7 Intelligent Connectivity: A New Capabilities to Bring Complex Use Cases -- 7.1 Introduction -- 7.2 Machine-to-Machine Communication and the Internet of Things -- 7.3 Convergence of Internet of Things, Artificial Intelligence and 5G -- 7.4 Intelligent Connectivity Applications -- 7.5 Challenges and Risks of Intelligent Connectivity -- 7.6 Recommendations -- 7.7 Conclusion -- 8 IoT: Laws, Policies and Regulations -- 8.1 Introduction -- 8.2 Recently Published laws and Regulations -- 8.3 Developing Innovation and Growing the Internet of Things (DIGIT) Act -- 8.4 General View -- 8.5 Relaxation of laws by the Federal Aviation Administration's (FAA) -- 8.6 Supporting Innovation of Self Driving Cars by Allowing Policies -- 8.7 Recommendations -- 8.8 Conclusion -- 9 Artificial Intelligence and Blockchain -- 9.1 Introduction -- 9.2 Decentralized Intelligence -- 9.3 Applications -- 9.4 How Artificial Intelligence and Blockchain will Affect Society -- 9.5 How Augmented Reality Works -- 9.6 Mixed Reality -- 9.7 Virtual Reality -- 9.8 Key Components in a Virtual Reality System -- 9.9 Augmented Reality Uses -- 9.10 Applications of Virtual Reality in Business -- 9.11 The Future of Blockchain -- 9.12 Blockchain Applications -- 9.13 Blockchain and the Internet of Things -- 9.14 Law Coordination -- 9.15 Collaboration for Blockchain Success -- 10 Digital Twin Technology -- 10.1 Introduction -- 10.2 The Timeline and History of Digital Twin Technology -- 10.3 Technologies Employed in Digital Twin Models -- 10.4 The Dimension of Digital Twins Models -- 10.5 Digital Twin and Other Technologies -- 10.6 Digital Twin Technology Implementation -- 10.7 Benefits of Digital Twin -- 10.8 Application of Digital Twins -- 10.9 Challenges of Digital Twins -- 11 Artificial Intelligence, Big Data Analytics, and IoT -- 11.1 Introduction -- 11.2 Analytic -- 11.3 AI Technology in Big Data and IoT -- 11.4 AI Technology Applications and Use Cases -- 11.5 AI Technology Impact on the Vertical Market -- 11.6 AI in Big Data and IoT Market Analysis and Forecasts -- 11.7 Conclusion -- 12 Digital Transformation Trends in the Automotive Industry -- 12.1 Introduction -- 12.2 Evolution of Automotive Industry -- 12.3 Data-Driven Business Model and data monetization -- 12.4 Services of Data-Driven Business Model -- 12.5 Values of New Services in the New Automotive Industry -- 12.6 Conclusion -- 13 Wireless Sensors/IoT and Artificial Intelligence for Smart Grid and Smart Home -- 13.1 Introduction -- 13.2 Wireless Sensor Networks -- 13.3 Power Grid Impact -- 13.4 Benefits of Smart Grid -- 13.5 Internet of Things -- 13.6 Internet of Things on Smart Grid -- 13.7 Smart Grid and Artificial Intelligence -- 13.8 Smart Grid Programming -- 13.9 Conclusion -- 14 Artificial Intelligence, 5G and IoT: Security -- 14.1 Introduction -- 14.2 Understanding IoT -- 14.3 Artificial Intelligence -- 14.4 5G Network -- 14.5 Emerging Partnership of Artificial Intelligence, IoT, 5G, and Cybersecurity -- 14.6 Conclusion -- 15 Intelligent Connectivity and Agriculture -- 15.1 Introduction -- 15.2 The Potential of Wireless Sensors and IoT in Agriculture -- 15.3 IoT Sensory Technology with Traditional Farming -- 15.4 IoT Devices and Communication Techniques -- 15.5 IoT and all Crop Stages -- 15.6 Drone in Farming Applications -- 15.7 Conclusion -- 16 Applications of Artificial Intelligence, ML, and DL -- 16.1 Introduction -- 16.2 Building Artificial Intelligence Capabilities -- 16.3 What is Machine Learning? -- 16.4 Deep Learning -- 16.5 Machine Learning vs. Deep Learning Comparison -- 16.6 Feature Engineering -- 16.7 Application of Machine Learning -- 16.8 Applications of Deep learning -- 16.9 Future Trends -- 17 Big Data and Artificial Intelligence: Strategies for Leading Business Transformation -- 17.1 Introduction -- 17.2 Big Data -- 17.2 Machine Learning-Based Medical Systems -- 17.3 Artificial Intelligence for Stock Market Prediction -- 17.3.1 Application of Artificial Intelligence by Investors -- 17.4 Trends in AI and Big Data Technologies Drive Business Innovation -- 17.5 Driving Innovation Through Big Data -- 17.6 The Convergence of AI and Big Data -- 17.7 How AI and Big Data Will Combine to Create Business Innovation -- 17.8 AI and Big Data for Technological Innovation -- 17.9 AI and Production -- 17.10 AI and ML Operations Research -- 17.11 Collaboration Between Machines and Human -- 17.12 Generative Designs -- 17.13 Adapting to a Changing Market -- 17.14 Conclusion -- Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
John Wiley and Sons
Keywords: Internet of things; 5G mobile communication systems; Artificial intelligence -- Industrial applications; Internet des objets; Communications mobiles 5G.; Intelligence artificielle -- Applications industrielles; 5G mobile communication systems; Artificial intelligence -- Industrial applications; Internet of things